The Perceived Cultural Barriers To Effective Communication Towards Patient Among Non-Saudi Registered Nurses Of A Public Hospital, The Kingdom of Saudi Arabia - Yee , Bit-Lian; Rosnida Abu Bakar,; Shahedan Saeidin, (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2020)
In the Kingdom of Saudi Arabia (KSA) health care setting effective communication is a central to the provision of compassionate and high-quality nursing care. The aim of the survey is to study the perceived cultural barriers to effective communication towards patient and knowledge towards culture working environment among non-Saudi registered nurses in a hospital in KSA. Methodology: This is cross-sectional survey conducted from January 2017 to Jun 2018 thorough self-administration questionnaire. The questionnaire was distributed to 150 nurses that randomly selected from medical and surgical fields and received feedback with total number 135 nurses. Results: Most of the respondents were female 125 (92.6%) between 26 to 30 years. In terms of years of experience, 49 (36.3%) had five to ten years of experience, and the rest 89 (65.9%) had no previous working experience in Saudi. The findings displayed that physical and mental tiredness for 55 (40.7%). The second ranked respondents strongly agreed that cultural communication barriers come from hard nursing tasks 45 (33.3%), heavy nursing workload 46 (34.1%) and followed by lack of information and skills in communication for which 50 (37.0%). Conclusion: The respondents considering communication barriers are related to personal and social characteristics, job specification, clinical situation of patients and environmental factors. There are significant results regarding the knowledge towards culture working environment in terms of nurses' perception, cultural norms and culture on life activities.(Abstract bu authors)